Ruin road - Giles, Lamar, 1979- (Scholastic Press, 2024)
High school football player Cade Webster buys a ring in a pawn shop, but when his wish that people stop acting scared of him seems to be coming true, he remembers the ring came with a warning--"When the strangeness begins, come back"-- and suddenly people seem to have lost their fear of everything.